Immigrant Students – challenge for national education in the perspective of the experience of the project “Portfolio of Integration” (POI) - Baranowska, Wanda; Kosiorek, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2014)
This article present the synthesis of experiences Polish teachers collected as a result of participation in POI project. Section 1 includes information about social and demographical context of immigration in Poland and teachers’ work in the project. Section 2 presents experiences in reference to the areas of integration in Poland, its typical aspects, all analysed during the course. Section 3 is a synthetic assessment of the usefulness of the Notebook of Integration, its testing results based on the profiles of the selected case studies of students.